AniDriveQA: a VQA dataset for driving scenes with animal presence - Wang, Rui; Wang, Ruiqi; Hu, Hao; Yu, Huai (Frontiers in Robotics and AI, 2025)
IntroductionAnimal-involved scenarios pose significant challenges for autonomous driving systems due to their rarity, unpredictability, and safety-critical nature. Despite their importance, existing vision-language datasets for autonomous driving largely overlook these long-tail situations.MethodsTo address this gap, we introduce AniDriveQA, a novel visual question answering (VQA) dataset specifically designed to evaluate vision-language models (VLMs) in driving scenarios involving animals. The dataset is constructed through a scalable pipeline that collects diverse animal-related traffic scenes from internet videos, filters and annotates them using object detection and scene classification models, and generates multi-task VQA labels with a large vision-language model. AniDriveQA includes three key task types: scene description, animal description, and driving suggestion.ResultsFor evaluation, a hybrid scheme was employed that combined classification accuracy for structured tasks with LLM-based scoring for open-ended responses. Extensive experiments on various open-source VLMs revealed large performance disparities across models and task types.DiscussionThe experimental results demonstrate that AniDriveQA effectively exposes the limitations of current VLMs in rare yet safety-critical autonomous driving scenarios. The dataset provides a valuable diagnostic benchmark for advancing reasoning, perception, and decision-making capabilities in future vision-language models.